The relationships among critical power determined from a 3-min all-out test, respiratory compensation point, gas exchange threshold, and ventilatory threshold - Bergstrom, H. C.; Housh, T. J.; Zuniga, J. M.; Traylor, D. A.; Camic, C. L.; Lewis, R. W.; Schmidt, R. J.; Johnson, G. O. (Research Quarterly for Exercise and Sport, 2013)
Purpose: Critical power (CP) from the 3-min test was compared to the power outputs associated with thresholds determined from gas exchange parameters that have been used to demarcate the exercise-intensity domains including the respiratory compensation point (RCP), gas exchange threshold (GET), and ventilatory threshold (VT). Method: Twenty-eight participants performed an incremental-cycle ergometer test to exhaustion. The VT was determined from the relationship between the ventilatory equivalent for oxygen uptake (VE/VO2) versus VO2 and the GET was determined using the V-slope method (VCO2 vs. VO2). The RCP was identified from the VE-versus-VCO2 relationship. CP was the average power output during the last 30 s of the 3-min all-out test. Linear regression was used to determine the power outputs associated with the RCP, GET, and VT, as well as the VO2 associated with CP. Mean differences among the associated power outputs, percent VO2 peak, and percent peak power output for the GET, VT, RCP, and CP were analyzed using separate one-way repeated-measures analyses of variance. Results: There were no significant differences between CP (187 ± 47 W) and the power output associated with RCP (190 ± 49 W) or between the power outputs associated with GET (139 ± 37 W) and VT (145 ± 37 W). The power outputs associated with GET and VT, however, were significantly less than were those at CP and associated with RCP. Conclusions: These findings suggest CP and RCP demarcate the heavy from severe exercise-intensity domain and result from a different mechanism of fatigue than that of GET and VT, possibly hyperkalemia.